Exploring Semantics and the Utilization of Figurative Language in the Song Lyrics of “21 Guns” by Green Day - Adika, Dimas; Budiarsana, Putu Agus (Yayasan Kyadiren, 2023)
Translation serves multiple purposes, encompassing the expression of emotions, the conveyance of ideas, and the ability to influence others. Figurative language plays a significant role in communicating feelings through the songs we encounter in our daily lives. This study adopts a descriptive qualitative approach to investigate this phenomenon. Content analysis is employed as the analytical technique, aiming to identify the distinct characteristics of messages conveyed through songs and the utilization of figurative language, such as metaphors, hyperboles, similes, euphemisms, and personifications. The findings reveal that the majority of lyrics within the song “21 Guns” contain implicit and profound meanings related to the physical and psychological impacts of war, including the destruction of homes and the loss of soldiers' lives. Furthermore, the song employs a diverse range of language styles, incorporating hyperbole and personification, which contribute to its captivating and meaningful nature